Konsep Ijtihad dan Hubungannya dengan Konsep Khatam Al-Nabiyyin - Wan Ali, Wan Zailan Kamaruddin (Jurnal Usuluddin, 1996)
Ijtihad, after the demise of the Holy Prophet (s.a.w) plays a vital role in daily Muslim life. In order to highlight the importance of Ijtihad, this article aims to discuss the concept of Ijtihad in general and its relevance with the concept of the End of Prophethood.